Impact of codon optimization on vip3Aa11 gene expression and insecticidal efficacy in maize - Li, Shengyan; Wen, Ning; Lv, Wenjie; Zhang, Mingjun; Wang, Yinxiao; Lang, Zhihong (Frontiers in Plant Science, 2025)
IntroductionCodon optimization is critical for high expression of foreign genes in heterologous systems. The vip3Aa11 gene from Bacillus thuringiensis is a promising candidate for controlling Spodoptera frugiperda.Methods and resultsTo develop insect-resistant maize, we designed two codon-optimized vip3Aa11 variants (vip3Aa11-m1 and vip3Aa11-m2) based on maize codon usage bias. Both recombinant proteins expressed in Escherichia coli exhibited high insecticidal activity. However, in transgenic maize, Vip3Aa11-m1 exhibited strong insecticidal activity against Spodoptera frugiperda and Spodoptera exigua, while Vip3Aa11-m2 lost activity despite identical amino acid sequences. RT-PCR analysis confirmed that both genes were transcribed correctly, but western blot results demonstrated a smaller product for vip3Aa11-m2, suggesting a translation-level alteration. Segment replacement and point mutation experiments in maize protoplasts demonstrated that the synonymous codon AAT (Asn) at the fourth amino acid position in vip3Aa11-m2 was associated with the production of a truncated protein, suggesting that the AAT codon may influence the selection of the translation initiation site, potentially shifting it to a downstream ATG (Met) codon.DiscussionThese findings not only reveal the critical role of codon context in translation initiation and protein integrity but also provide a novel strategy for optimizing foreign genes in crop improvement, particularly offering valuable insights for engineering insect-resistant maize using Bt genes.